2012
DOI: 10.1116/1.4737160
|View full text |Cite
|
Sign up to set email alerts
|

Carbon contamination and oxidation of Au surfaces under extreme ultraviolet radiation: An x-ray photoelectron spectroscopy study

Abstract: Articles you may be interested inProbing temporal evolution of extreme ultraviolet assisted contamination on Ru mirror by x-ray photoelectron spectroscopy J. Vac. Sci. Technol. B 30, 021601 (2012); 10.1116/1.3680122 X-ray photoelectron spectroscopic study of the formation of catalytic gold nanoparticles on ultraviolet-ozone oxidized GaAs ( 100 ) substrates Extreme ultraviolet (EUV) radiation-induced carbon contamination and oxidation of Au surfaces were investigated using x-ray photoelectron spectroscopy (XPS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…4(a). This minor oxygen presence in the surface is most likely due to some water adsorption on the target surface occurred after the irradiation process [47]. High resolution XPS of the W-4f region (Fig.…”
Section: Results and Discussion A Effect Of He + Ion Fluencementioning
confidence: 99%
“…4(a). This minor oxygen presence in the surface is most likely due to some water adsorption on the target surface occurred after the irradiation process [47]. High resolution XPS of the W-4f region (Fig.…”
Section: Results and Discussion A Effect Of He + Ion Fluencementioning
confidence: 99%
“…The appearance of the carbon species in the XPS sample obtained with the gold film is consistent with the early literature that the ambient chemicals can rapidly be adsorbed onto the gold surfaces. 48,49 Ag + Adsorption onto the BuT-Functionalized Gold. Direct evidence showing the Ag + binding to the BuTfunctionalized gold are shown with the XPS measurements (Figure 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…19 Additionally, the XPS peak indicating adsorbed atomic oxygen, which should appear at lower binding energy, was not observed. 25,26 We also observed that the oxygen network is stable at room temperature.…”
Section: ■ Results and Discussionmentioning
confidence: 59%